The CVS Beauty in Real Life campaign - Robson, Karen (London : SAGE Publications: SAGE Business Cases Originals, 2019)
CVS Health, one of the leading drug stores in the U.S. pharmacy industry, had recently announced their "Beauty in Real Life" campaign, which declares that the company would no longer use airbrushing in their beauty product marketing images. Images that had not been digitally enhanced would bear the CVS Health "beauty mark" label, signaling their untouched nature. By 2020, the company plans to have all marketing images of beauty products sold in their store--including those by other brands--labeled in such a way as to signal whether they were digitally altered or not. This move, inspired by the company mission to promote health, set CVS Health apart from other competitors in the industry. In this case, students are asked to evaluate whether the use of airbrushing on beauty product marketing images constitutes deceptive advertising, as well as to evaluate the "Beauty in Real Life" campaign itself.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; CVS/pharmacy (Firm) -- Case studies; Advertising campaigns -- Planning -- Case studies; Advertising media planning -- Case studies; Marketing -- Planning -- Case studies; Drugstores -- United States -- Case studies